DETERMINAÇÃO DAS CONCENTRAÇÕES TOTAIS E BIOACESSÍVEIS DE ÍONS METÁLICOS EM MATRIZES ALIMENTARES EMPREGANDO ESPECTROMETRIA DE ABSORÇÃO ATÔMICA - ANDRADE, CAMILA KULEK DE (2018)
Food and beverages, such as yogurt and mate tea, are some of the main routes of ingestion of metal ions that, depending on concentration and speciation in the food matrix, have important biological functions in the organism. However, should be controlled the amount of ingestion of these elements, since the lack or excess of them can cause adverse effects for living beings. Normally, in quality control and food safety is used the total concentration of elements in food matrices. However, should be assessed the bioaccessibility of metal elements in food and beverages, since this parameter estimates the amount to be absorbed from them or their possible nutritional or toxic function in the route of human ingestion-digestion-absorption. Thus, the aim of this work was first to determine the total concentration of Zn, Cu, Cr, Cd and Pb in yogurt samples, proposing a fast and direct methodology, by slurry sampling allied to Atomic Absorption Spectrometry - AAS (FAAS and GF AAS). For this, as dispersion medium of yogurt to prepare the suspensions were used solutions of HNO3 and HCl. In addition to the optimization of the heating program of the graphite furnace, performed for each metal trace in the matrix, it was validated the proposed method, being possible to obtain adequate sensitivity, with precision and accuracy. Based on the PBET (Physiologically Based Extraction) method with the simulation of human digestion processes using gastric juice (pepsin extracted from porcine gastric mucosa and HCl) and intestinal juice (pancreatin extracted from swine pancreas, bile salts and NaHCO3) were performed in vitro gastrointestinal digestion assays. The incubation process for the gastric and intestinal digestion stages was performed for 2 hours at 37 ºC and agitation (150 rpm) simulating the human conditions of temperature and peristaltic movements. After centrifugation (10000 rpm, 4 °C, and 20 min) the bioaccessible fractions were obtained, and the metal ion concentrations were quantified by analytical curve with external standardization using AAS. Twenty-five samples of yogurt from 6 different brands were analyzed, with consistency and varied flavors. Zn and Cu were quantified in all samples, with mean concentrations of 7.2 ± 7.5 μg g-1 and 103.4 ± 151.5 ng g-1, respectively. These concentrations are in agreement with the literature, and are comparable to those available in the Brazilian Table of Food Composition (in Portuguese Tabela Brasileira de Composição de Alimentos - TACO) - 200 ng of Cu in 1g yogurt, and 3 to 5 μg of Zn per gram of yogurt. Cr, Pb and Cd were quantified in less than 36% of the samples, and the mean concentrations (ng g-1) for these metals were 2.4 ± 1.4 (Cd) at 37.4 ± 11.9 (Pb). Regarding the bioaccessible fractions, for the elements considered essential, it was observed the order Cr > Cu > Zn. Cr and Cu presented the highest bioaccessible fractions from yogurt, with averages of 102 ± 12% and 87 ± 18%, respectively. Considering the biological functions performed by metals such as Cr(III) and Cu, a high bioaccessibility of these metals is desirable. Although Zn is an essential element, the metal from the yogurt presents low values for bioaccessible fractions (24 ± 7%). For Pb and Cd, the bioaccessible fractions were 33 ± 5% and 1.6 ± 2.4%, respectively. Lower bioaccessible fractions for these metals are desirable considering their toxicity. Based on the metal intake calculations, considering the bioaccessibility from the yogurt, the mean values in relation to the recommended daily intake (RDI) or tolerable limit for intake of metals varied from 0.003% (Cd) to 2.5% (Zn). In this case, yogurt intake is safe in relation to toxic elements such as Pb and Cd. However, it cannot be considered a source of essential elements such as Cr, Cu and Zn. For mate tea, total concentrations of Al, Zn, Cu, Cr, Cd and Pb were determined in decoctions prepared by heating the commercial product with ultrapure water using AAS. Of the same manner as for yogurt, using gastric and intestinal juices, it was performed the in vitro bioaccessibility. The studies with 20 samples of mate tea (3 brands), with different flavors and/or lots, acquired in the local commerce were conducted. The mean concentrations of metal ions determined in mate tea decoctions ranged from 50 ± 24 ng g-1 (Cd) to 60 ± 18 μg g-1 (Al). The variability between the concentrations of metals and the samples may be related to the place of cultivation of yerba mate or even to the industrial process involved in the production of tea. Through Principal Component Analysis (PCA) were analyzed the data obtained, and a separation of the samples was observed (with a greater emphasis on brands 1 and 2) according to the brand of the product and the concentration of the evaluated metals. Regarding bioaccessibility, the release of the metals considered nutrients of the beverage followed the order of Cr ≥ Cu > Zn, representing 41 to 85% of the total concentration of the elements. For the elements that do not possess known biological activity, the order of bioaccessibility was Al >> Cd > Pb. Although the Cd presented the lowest levels in the decoction, its bioaccessible fraction was about 52% of the total concentration. For Al and Pb, the bioaccessible fractions were 100% and 19%, respectively. Therefore, Al is an element present in mate tea in high concentrations and in fully bioaccessible form. From the bioaccessibility values, the daily intake of the metals was calculated, and the results indicated that the consumption of mate tea decoction gives small amounts of metals to the organism, representing about 0.008% (Pb) to 0,6% (Al) of the acceptable concentrations for the ingestion of these elements. Therefore, the mate tea decoction for the evaluated samples presents food safety in relation to the metallic species studied, presenting no risk of toxicity in relation to non-essential metals (Al, Cd and Pb), nor nutritive potential in relation to essential metals (Zn, Cu and Cr).